An Archaeological Exploration of a Settlement at Dixie Plantation, Hollywood, SC - Falls, Eva E. (East Carolina University, 2014)
The College of Charleston's Dixie Plantation in Hollywood, SC is located 19 miles west of the College of Charleston's main campus in downtown Charleston. Dixie Plantation was formerly an 18th and 19th century rice and cotton plantation known as Dixie Plantation. Today, the avenue of oaks and the remnants of rice canals are all that is left of the former plantation. A 1799 and a ca.1807 plat map of the area indicates the plantation once consisted of a main house, an avenue of oaks, and an unidentified settlement, simply labeled "Fickling's" on the ca. 1807 map. This settlement was represented by two structures on the 1799 map and then four structures on the 1807 map. There are no intact architectural remains of the structures indicated on the plat maps, but in the fall of 2012, an archaeological survey of the area was completed. The primary research goals of this project were to identify the location the settlement indicated by these maps, establish an occupation period, and determine the function of these four buildings from the collected artifact assemblage. Due to high percentage of table wares and kitchen artifacts at the site, the evidence suggests the buildings had a residential component and could be residences of some of the plantation dependents, particularly the enslaved workers. This thesis will discuss the challenges of identifying sites based on historic maps and assigning site function for the settlement.
Keywords: Archaeology; Slavery; South Carolina; Excavations (Archaeology)--South Carolina--Charleston County; Plantation life--South Carolina--Charleston County; Charleston County (S.C.)--Antiquities; Dixie Plantation (Charleston County, S.C.); Plantations--South Carolina